Pengaruh Media Terhadap Pertumbuhan Metarhizium Anisopliae dan Virulensinya Pada Larva Tenebrio Molitor - Kresnatita, Susi; Surawijaya, Panji; Pituati, Grisly; Barus, Widya Pitaloka BR; Supriati, Lilies (Jurnal Penelitian UPR, 2025)
The aim of this research was to study the effect of adding nut extract or coconut water to PDA media on the growth and virulence of Metarhizium anisopliae in Tenebrio molitor larvae. The research used a Completely Randomized Design (CRD) with 5 treatments and 4 replications. The treatments tested consisted of; PDA media), KH = PDA media + 10% green bean extract, KM = PDA media + 10% red bean extract, KK = PDA media + 10% soybean extract, and K = PDA media + 20% coconut water. The observed variables consisted of; colony diameter, spore density per mL and T. molitor larvae mortality. The results of the study showed that the addition of nut extract or coconut water to PDA media had a very significant effect on the growth of the diameter of the M. anisopliae colony and the mortality of T. molitor larvae. The treatment of PDA media + 10% soybean extract and the treatment of PDA media + 20% coconut water had the same M. anisopliae colony growth at 24 dai of 90 mm which was significantly higher than the other media treatments, having a higher spore density of 155 x 106 and 105 x 106 per ml, respectively. Mortality of T. molitor larvae in the KK and K treatments at 16 daa of M. anisopliae spore suspension was 95% and 91.25%, respectively. The KK and K treatments were the best treatments for colony diameter growth, as well as the greatest mortality of T. molitor larvae.